Diagnostic Utility of Biplex/Multiplex Polymerase Chain Reaction in Infectious Granulomatous Dermatitis in North Indian Population. (August 2021) - Parkhi, Mayur; Kumar S, Mukin; De, Dipankar; Yadav, Rakesh; Sethi, Sunil; Radotra, Bishan Dass; Saikia, Uma Nahar
Abstract : Background: A definite diagnosis of infectious granulomatous dermatitis (IGD) is difficult for both practicing dermatologists and dermatopathologists due to overlapping clinical and histomorphological features. We aimed to explore the role of multiplex polymerase chain reaction (PCR) for identifying a definite etiological agent for diagnosis and appropriate treatment in IGD in formalin-fixed paraffin-embedded tissue. Materials and Methods: Sixty-two cases of IGD were included, excluding leprosy. The histochemical stains including Ziehl–Neelsen, periodic acid–Schiff, and Giemsa were performed in all cases. A multiplex PCR was designed for detection of tuberculosis (TB) (IS6110 and mpt64), fungal infections (ITS1, ITS2; ZM1, and ZM3), and leishmaniasis (kDNA). The results of histomorphology, histochemical stains, and multiplex PCR were compared. Results: Among 62 cases, the sensitivity rate of PCR detection for organisms was 16.7%, 0%, 100%, 72%, 75%, and 66.7% in patients with TB, suggestive of TB, leishmaniasis, fungal infections, and granulomatous dermatitis not otherwise specified and granulomatous dermatitis suggestive of fungus, respectively. The TB PCR using IS6110 primers was negative in all cases; however, PCR using mpt64 primers was positive in 33.33% cases of scrofuloderma. The histochemical stains including Ziehl–Neelsen for acid-fast bacilli, periodic acid–Schiff for fungus, and Giemsa for Leishman-Donovan bodies showed positivity in 11.3%, 43.5%, and 3.2%, respectively. Conclusion: A multiplex PCR ( Mycobacterium tuberculosis, Leishmania, and panfungal) is highly recommended in all cases of IGD where an etiological agent is difficult to establish by skin biopsy and histochemical stains along with a clinicopathological correlation. This will augment in appropriate treatment and will reduce empirical treatment and morbidity in such patients.